An in vitro study of the antimicrobial property of the leaves of persea americana mill. (Avocado) against bacteria present in supragingival plaque - David, Janina Camille B.; Leonor, Sheila Anne D.; Mendoza, Michael Antonio F. (Adviser).
The purpose of this study was to determine the antimicrobial property of the leaves of Persea americana Mill. (avocado) against bacteria present in supragingival plaque. An avocado leaf decoction was tested on plaque samples collected from patients with Moderate to Severe Gingivitis, using Chlorhexidine as positive control and no treatment as negative control. Bacterial load Reduction Test was performed, and the antimicrobial property was determined based on the number of colony forming units. Results showed that the antimicrobial property of the test group is not statistically significant as compared with the negative control group. In conclusion, the results of the present study have shown that the leaves of Persea americana Mill. (avocado) do not have antimicrobial property against bacteria present in supragingival plaque since there is an insignificant reduction in bacterial load.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Herbal medicine; Dental plaque; Anti-infective agents; Avocado--Anti-infective agents